Improvement of arterial wall characteristics by the low-dose fluvastatin and valsartan combination in type 1 diabetes mellitus patients. (September 2013) - Savić, Vedran; Eržen, Barbara; Janić, Miodrag; Lunder, Mojca; Boncelj, Maja; Kanc, Karin; Janež, Andrej; Šabovič, Mišo
We tested whether short-term, low-dose treatment with the fluvastatin and valsartan combination could improve impaired arterial wall characteristics in type 1 diabetes mellitus patients. A total of 44 type 1 diabetes mellitus patients were randomised into the treatment group [ n = 22; received a low-dose combination of fluvastatin (10 mg daily) and valsartan (20 mg daily)] and the control group ( n = 22; received placebo), both for 30 days. Brachial artery flow-mediated dilation (FMD), pulse wave velocity (PWV) and carotid artery β-stiffness were measured. Significant improvements in FMD (+73.2%), PWV (−7.5%) and β-stiffness (−10.0%) were achieved after 1-month treatment compared to the control group (all p values < 0.001). Three months after therapy discontinuation, important residual improvement in measured parameters was still present. No changes in lipids and blood pressure accompanied the beneficial improvements. We conclude that relatively simple intervention (low-dose, short-term fluvastatin/valsartan combination) produces substantial, long-term improvement of arterial wall characteristics in type 1 diabetes mellitus patients.